Obraz wzrokowych potencjałów wywołanych w cukrzycy typu 1. - Szabela, Dariusz A.; Loba, Jerzy; Pałenga-Pydyn, Dorota; Tybor, Krzysztof; Ruxer, Jan; Split, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The aim of this study was to assess frequency of abnormal visual evoked potentials in type 1 diabetic patients and the correlation between patients' age, duration of the disease, metabolic control and coexisting clinical complications on the abnormal recordings. The investigation was carried out in a group of 50 diabetic patients, aged from 16 to 55 years. The VEP recordings were performed four times, each time using a pattern made up of elements of another size (18, 36, 72 and 144 angular minutes). With this method the abnormal VEP were recorded in 26% of the cases and it was possible to find 10% patients who had more than one abnormal test. In VEP recorded with stimulation with a single size pattern, abnormal results were recorded from 8% to 14% of the cases. The pathological VEP were recorded as elongation of P100 latency in 86% type 1 diabetic patients, and as significant difference between the latencies from both eyes in 14% cases. There was no statistically significant correlation between the age, duration of the disease, coexisting clinical complications or metabolic compensation and the abnormal recordings.